How important is importance for prospective memory? A review - Walter, Stefan; Meier, Beat (Frontiers in Psychology, 2014)
Forgetting to carry out an intention as planned can have serious consequences in everyday life. People sometimes even forget intentions that they consider as very important. Here, we review the literature on the impact of importance on prospective memory performance. We highlight different methods used to manipulate the importance of a prospective memory task such as providing rewards, importance relative to other ongoing activities, absolute importance, and providing social motives. Moreover, we address the relationship between importance and other factors known to affect prospective memory and ongoing task performance such as type of prospective memory task (time-, event- or activity-based), cognitive loads, and cue focality. Finally, we provide a connection to motivation, we summarize the effects of task importance and we identify important venues for future research.